The Adaptability, Biomass Production and Nutritional Value of Introduced Grasses in Timor-Leste - Deus, Pedro de; Sutaryono, Y. A.; Gunartha, I. G. E. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
An experiment was conducted and aimed to determine the adaptability, fresh biomass, drymatter and nutritional value of grasses introduced from overseas to Timor-Leste. The experimentwas conducted at the Research Center of the Ministry of Agriculture and Fisheries of Timor-Leste islocated in Loes, the Village of Guguleur, Sub-District Maubara and District LiquiÃ§a. The researchmaterial consisted of Brachiaria hybrid cv Mulato, Setaria sphacelata, Pennisetum purpureophoidesand Panicum maximum. The grasses were layouted using Randomized Complete Block Design(RCBD) and each grass was replicated four times. Variables measured consisted of plant height,clump circumferences, fresh biomass and dry matter and nutritional value. Data were analyzed usingANOVA Meta-Experiments and multiple regression analysis. The orthogonal contrast was used tofind the treatments that show the significant different effect. The result showed that theprecipitation, temperature, solar radiation and relative humidity affected the performance of grasson plant height but did not significant affect in circumference clumps and fresh biomass.Furthermore, those facts were explained in the result of ANOVA Meta-Experiment, where theinfluence of the season, the type of grass and the interaction between the season and the type ofgrass showed a highly significant (P<0.01) to the fresh biomass. The influence of the season, theinteraction of the season and the type of grass have no effect on grass dry matter (P>0.05). Althoughthe biomass production is lower, the nutritional values of the grasses do not vary compare to grassesplanted in Indonesia. The grasses are suitable for planting and developing in Timor-Leste as animalfeed in the future.Key Words: Adaptability, Biomass, Dry Matter, Nutritional Value, Timor-Leste, Grasses